2014
DOI: 10.1038/tp.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of plasma metabolites in first-episode schizophrenia: a capillary electrophoresis time-of-flight mass spectrometry study

Abstract: Few biomarkers have been known that can easily measure clinical conditions in mental illnesses such as schizophrenia. Capillary electrophoresis time-of-flight mass spectrometry (CE-TOFMS) is a new method that can measure ionized and low-molecular-weight metabolites. To explore global metabolomic alterations that characterize the onset of schizophrenia and identify biomarkers, we profiled the relative and absolute concentrations of the plasma metabolites from 30 patients with first-episode schizophrenia (FESZ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 55 publications
4
56
2
Order By: Relevance
“…Upregulation of plasma homocysteine is associated with various physical illnesses such as arterial sclerosis, thus the eliminative role of betaine is suggested to be crucial to homeostasis [32, 33]. Increasing levels of homocysteine also induce inflammation in the brain via increasing oxidative stress and inflammatory cytokines, and a recent study revealed a lower plasma concentration of betaine in patients with first-episode schizophrenia [34]. Based on the above evidence, betaine is suggested to play important roles in expressing mental dysfunctions including depressive mood by regulating the BHMT reaction and the following systematic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of plasma homocysteine is associated with various physical illnesses such as arterial sclerosis, thus the eliminative role of betaine is suggested to be crucial to homeostasis [32, 33]. Increasing levels of homocysteine also induce inflammation in the brain via increasing oxidative stress and inflammatory cytokines, and a recent study revealed a lower plasma concentration of betaine in patients with first-episode schizophrenia [34]. Based on the above evidence, betaine is suggested to play important roles in expressing mental dysfunctions including depressive mood by regulating the BHMT reaction and the following systematic changes.…”
Section: Discussionmentioning
confidence: 99%
“…23 Two studies using this technique showed robust changes in four molecules (arginine, taurine, 5-oxoproline and lactic acid) in the plasma of autism spectrum disorders, 24 and significant changes in the five molecules (creatine, betaine, nonanoic acid, benzoic acid and perillic acid) in the plasma of first-episode, medicated patients with schizophrenia. 25 However, there are no reports using this technique in CSF samples from BD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies applying metabolomic profiling of patient serum are also starting to be used to explore the biology of psychiatric disorders [41,42,43,44,45,46]. Such studies have suggested the possibility of identifying biomarkers for schizophrenia [47,48,49,50,51,52], major depressive disorder [53,54] and posttraumatic stress disorder [55], and have also been used to study medication-induced metabolic changes [56,57]. In bipolar disorder, metabolomic studies have been undertaken in urine samples to identify potential biomarkers [58,59,60,61].…”
Section: Discussionmentioning
confidence: 99%